The neutral amino acid transporter SLC7A10 in adipose tissue, obesity and insulin resistance - Jersin, Regine Åsen; Jonassen, Laura Roxana; Dankel, Simon Nitter (Frontiers in Cell and Developmental Biology, 2022)
Obesity, insulin resistance and type 2 diabetes represent major global health challenges, and a better mechanistic understanding of the altered metabolism in these conditions may give improved treatment strategies. SLC7A10, a specific member of the SLC7 subfamily, has recently been implicated as an important modulator of core processes in energy- and lipid metabolism, through its selective expression in white adipocytes. In human cohorts, adipose SLC7A10 mRNA shows strong inverse correlations with insulin resistance and components of the metabolic syndrome, strong heritability, and an association with type 2 diabetes risk alleles. SLC7A10 not only serves as a marker of white adipocytes, but its overexpression has recently been shown to lower the generation of reactive oxygen species (ROS) and stimulate mitochondrial respiratory capacity. Conversely, inhibition of SLC7A10 has in mouse and human adipocyte cultures been found to increase ROS and lipid accumulation, likely explained by lowered serine uptake and glutathione production. In zebrafish, loss-of-function Slc7a10 resulted in greater diet-induced body weight and larger visceral adipocytes. At the same time, loss of Slc7a10 in mouse white preadipocytes was found to increase the formation of thermogenic beige adipocytes. Taken together, the data point to an important but complex role of SLC7A10 in metabolic regulation across different adipose tissue depots and adipocyte subtypes. Further research into SLC7A10 functions and related SLCs, including its possible reliance on the binding partner SLC3A2, may lead to new precision therapeutics for mitigating the risk of insulin resistance and type 2 diabetes among people with obesity.